Application of Gaussian optical tweezers for ultrafast laser assisted direct-write nanostructuring - Quentin, Ulf-Hermann; Leitz, Karl-Heinz; Alexeev, Ilya; Schmidt, Michael (Journal of Laser Micro Nanoengineering, 2012)
The minimal size of optically generated structures is always affected by diffraction. This fundamental limitation does not allow laser radiation to be focussed much smaller than half of its wavelength and therefore it also limits minimal feature sizes of laser produced structures. In near-field optics, however, the diffraction limit does not apply, which in principal allows for tighter focussing. In this contribution, a flexible approach for direct-write nanostructuring is presented. Dielectric micro-particles are positioned by Gaussian optical tweezers and irradiated by ultrafast laser pulses. The particles focus the pulses and enable surface structuring.
Created from Fastlane, Scopus look-up
Keywords: Direct-write; Nanostructuring; Optical trap; Ultrafast lasers